The development of an immune inspired energy charging mechanism for swarm robotic system - Al Haek, Mohammed (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2016)
Swarm Robotics is a part of Swarm Intelligence, which is inspired by insects, birds and other social animals, and concerned with controlling and coordinating multiple small robots. Swarm Robotics has several advantages, and one of its most important criteria is robustness or fault tolerance. However, recent research showed that swarm robotics systems can be affected by the continuous failure of members of the swarm, thus reflecting on the overall performance. We propose an energy charging mechanism inspired by an immune system response known as granuloma formation. The granuloma formation is a process by which unwanted substances are removed by immune systems. This research presents a study of a particular immune systems response for inspirations on energy charging in swarm robotic systems. To understand the process of granuloma formation so that relevant components can be abstracted and logically extracted, a model of granuloma formation using Unified Modelling Language is developed. Then armed with this model, an agent based simulation is constructed to allow further understanding of the agents involved in the process of forming a granuloma. Based on this model and the simulation, analogous properties of granuloma formation and swarm robotic systems are mapped accordingly. Then, immune inspired energy charging mechanism is developed. The proposed energy charging mechanism is presented, simulated and compared with another conventional energy charging mechanism, which is the use of contact-less energy charging area. Built on the experimental results, the proposed mechanism shows an improvement in terms of performance time and aggregate energy of the swarm.